Temporary sound barrier system from natural fiber polymeric composite - Hanim Mohamed Ariff, Azmah; Dele-Afolabi, Temitope T.; Hossain Rafin, Tahrim; Jung, Dong-Won; Leman, Zulkiflle; Anas Md Rezali, Khairil; Calin, Recep (Elsevier Ltd, 2023)
Sound barriers, rather than shutting off the source of noise, are the most effective method for reducing noise pollution and reducing the intensity from diverse sources. In the present study, a natural fiber was employed alongside a polymer material to produce a sound barrier system. The natural fiber composite used was Rice Husk-PU reinforced composite. The harmonic analysis was performed through ANSYS to evaluate the sound absorbing coefficient and transmission loss. More so, the stress–strain analysis with the total deformation of the panel has been analyzed. In order to have better understanding of the sound absorption coefficient and transmission loss, the frequency range on the simulation was set between 0 and 4000 Hz. The result showed better sound absorption coefficient on the lower frequency region when compared with standard and measured results from published paper. It also simulated higher transmission loss at a high frequency region since high frequency means high sound intensity level. For the validation of the simulated results, the data were compared with the tested experimental results for the same material and a very small difference was observed.